ENHANCING ENGLISH SPEAKING MOTIVATION OF NURSING STUDENTS’ THROUGH MINI VLOGS ON TIKTOK - BURA, BERNADETHA OVIATY; BALIK, LUSIYANA MARIETA; URAN, STEFANUS IGOLOIS GRENGA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research explored the use of TikTok mini-vlogs as a medium to enhance the motivation and English-speaking skills of eleventh grade students at the Catholic Private School of St. John Paul II Maumere. The study aimed to address the students' challenges in speaking English, such as limited vocabulary, low confidence and lack of motivation. Utilizing the Classroom Action Research (CAR) methodology, the research was conducted in two cycles. Data were collected through pre-test and post-test, with assessment focusing on fluency, pronunciation, non-verbal communication, content and creativity. The results showed significant improvements in all aspects assessed. A very significant improvement occurred in fluency and creativity. The average score for fluency improved from 3.62 in Cycle I to 4.62 in Cycle II, representing a 1.0-point gain and the average score for creativity improved from 3.14 in Cycle I to 4.4 in Cycle II, which indicates an improvement of 1.26. This shows that the implementation of mini vlog on TikTok application in the learning process can overcome educational issues, especially in learning English as a second language. ABSTRAKPenelitian ini mengeksplorasi penggunaan mini-vlog TikTok sebagai media untuk meningkatkan motivasi dan keterampilan berbicara bahasa Inggris siswa kelas sebelas di Sekolah Swasta Katolik St. John Paul II Maumere. Studi ini bertujuan untuk mengatasi tantangan yang dihadapi siswa dalam berbicara bahasa Inggris, seperti kosakata yang terbatas, kurangnya kepercayaan diri, dan kurangnya motivasi. Menggunakan metodologi Penelitian Tindakan Kelas (PTK), penelitian ini dilakukan dalam dua siklus. Data dikumpulkan melalui pre-test dan post-test, dengan penilaian yang berfokus pada kelancaran, pengucapan, komunikasi non-verbal, konten, dan kreativitas. Hasilnya menunjukkan peningkatan signifikan dalam semua aspek yang dinilai. Peningkatan yang sangat signifikan terjadi dalam kelancaran dan kreativitas. Skor rata-rata untuk kelancaran meningkat dari 3,62 pada Siklus I menjadi 4,62 pada Siklus II, yang mewakili peningkatan sebesar 1,0 poin, dan skor rata-rata untuk kreativitas meningkat dari 3,14 pada Siklus I menjadi 4,4 pada Siklus II, yang menunjukkan peningkatan sebesar 1,26. Ini menunjukkan bahwa penerapan mini vlog di aplikasi TikTok dalam proses pembelajaran dapat mengatasi masalah pendidikan, terutama dalam pembelajaran bahasa Inggris sebagai bahasa kedua.